Modelling the transmission dynamics of Ebola infection - Anorue†, F.O; Okwara*, O.R. (International Journal of Mathematical Analysis and Modelling, 2023)
Since not all infectious diseases have been kept under control because of the diversity of pathogens and means of transmission not well known, the adequate control measure to be implemented is impeded or hampered. Working on Ebola disease, we formulated a modified SEIR model to describe the transmission dynamics of the virus. This model considered the environmental contaminant and primates as major factors in the transmission dynamics alongside with infectious humans. Mathematical analysis carried out showed that the disease freeequilibrium is locally and globally asymptotically stable, when the reproduction number